2020
DOI: 10.3390/diagnostics10090661
|View full text |Cite
|
Sign up to set email alerts
|

Design, Validity, and Reliability of a New Test, Based on an Inertial Measurement Unit System, for Measuring Cervical Posture and Motor Control in Children with Cerebral Palsy

Abstract: Objective: The aim of this study was to design and propose a new test based on inertial measurement unit (IMU) technology, for measuring cervical posture and motor control in children with cerebral palsy (CP) and to evaluate its validity and reliability. Methods: Twenty-four individuals with CP (4–14 years) and 24 gender- and age-matched controls were evaluated with a new test based on IMU technology to identify and measure any movement in the three spatial planes while the individual is seated watching a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…This means the lower part of the body will be stationary and will not affect head movement, as a result only one IMU has been used to capture the head movement. Additionally, different studies showed that one IMU can capture the full head orientation [24,[51][52][53].…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…This means the lower part of the body will be stationary and will not affect head movement, as a result only one IMU has been used to capture the head movement. Additionally, different studies showed that one IMU can capture the full head orientation [24,[51][52][53].…”
Section: Measurementsmentioning
confidence: 99%
“…The main contribution of this paper is the use of a custom built and low-cost sensor for capturing head movement of children with CP in the age range of 2 to 5 years. Most of the research in the literature target older children (5-12 years) with either higher CP levels such as level I or II, where the child already has better motor ability and reasonably good head control [23][24][25]. The paper shows the application of a low-cost engineering solution to capture clinically viable data which allows clinical professionals and physiotherapists to get a better understanding of the active range of head movement for children with CP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wearable accelerometers have long been used in research to record body segment orientation and motion [ 1 , 2 , 3 ]. Over the past decade, Inertial Measurement Units (IMUs) have become a research tool of choice for field-based quantification of kinematics and joint angles [ 4 , 5 ]. By combining the outputs of the gyroscope, accelerometer, and magnetometer componentry, IMUs are able to capture dynamic movement data accurately and reliably [ 6 ].…”
Section: Introductionmentioning
confidence: 99%